Enzootic bovine leukosis in a cow - Santos, Igor R.; Henker, Luan C.; Kemper, Regina T. (Brazilian Journal of Veterinary Pathology, 2023)
A 5-year-old, Holstein-Friesian dairy cow was evaluated by a veterinary practitioner for a 30-day history of unilateralexophthalmos (Fig. 1). After 15 days, the cow presented lameness followed by progressive weight loss and pelvic limbs paresis,culminating in persistent sternal recumbency (Fig. 2). The superficial inguinal lymph nodes were enlarged. Due to the poorprognosis, the cow was euthanized and submitted to a postmortem examination.